WHY COULD CHILDREN NOT SURVIVE IN SCHOOLS? A CASE STUDY AT THE BAJO COAST - Sudirman, Sudirman; Haling, Abd. (JURNAL EDUSCIENCE, 2024)
The majority of children belonging to the Bajo tribe, residing on the coast of Bone Bay, do not complete their primary education. They are unable to remain in education until they have completed their studies. The objective of this study is to elucidate the underlying factors that contribute to the phenomenon of Bajo children dropping out of school. This research employed a qualitative approach utilising a case study design and a purposive sampling technique. The research subjects concentrated their attention on two primary schools where children belonging to the Bajo ethnic group are enrolled. Classroom and document observations were conducted, as well as unstructured interviews with two principals four teachers, and 12 Bajo children. The data were subjected to descriptive and qualitative analysis. The findings of this study indicate that four factors contribute to the inability of Bajo children to remain in school. These factors are (1) unsupportive environment, (2) irrelevant living habits, (3) inappropriate learning strategies at school, and (4) dense subject matter. The findings of this study have implications for school authorities, who should consider developing kinesthetic learning models in accordance with the environmental, social and familial characteristics of Bajo children. Further research is needed to clarify how to develop students' pro-environment syllabus with kinesthetic-based learning models.